A Preliminary Study to Investigate the Genetic Background of Longevity Based on Whole-Genome Sequence Data of Two Methuselah Dogs - Jónás, Dávid; Sándor, Sára; Tátrai, Kitti; Egyed, Balázs; Kubinyi, Enikö (Frontiers in Genetics, 2020)
Aging is the largest risk factor in many diseases and mortality alike. As the elderly population is expected to increase at an accelerating rate in the future, these phenomena will pose a growing socio-economic burden on societies. To successfully cope with this challenge, a deeper understanding of aging is crucial. In many aspects, the companion dog is an increasingly popular model organism to study aging, with the promise of producing results that are more applicable to humans than the findings that come from the studies of classical model organisms. In this preliminary study we used the whole-genome sequence of two extremely old dogs – age: 22 and 27 years (or 90-135% more, than the average lifespan of dogs) – in order to make the first steps to understand the genetic background of extreme longevity in dogs. We identified more than ~80 thousand novel SNPs in the two dogs (7500 of which overlapped between them) when compared to 3 publicly available canine SNP databases, which included SNP information from850 dogs. Most novel mutations (~52000 SNPs) were identified at noncoding regions, while 4.6% of the remaining SNPs (n~1600) were at exons, including 670 missense variants – 76 of which overlapped between the two animals – across 472 genes. Based on their gene ontologies, these genes were related – among others – to gene transcription/translation and its regulation, to immune response and the nervous system in general. We also detected 12 loss-of-function mutations, although their actual effect is unclear. Several genetic pathways were also identified, which pathways may be tempting candidates to be investigated in large sample sizes in order to confirm their relevance in extreme longevity in dogs (and possibly, in humans). We hypothesize a possible link between extreme longevity and the regulation of gene transcription/translation, which hypothesis should be further investigated in the future. This phenomenon could define an interesting direction for future research aiming to better understand longevity. The presented preliminary results highlight the utility of the companion dog in the study of the genetic background of longevity and aging.